Kontroversi Pemaknaan Nasikh dan Mansukh: Kajian Surah Al-Imran Ayat 93 (Perspektif Tafsir Jalalain dan Tafsir Ibnu Katsir) - Agita Yurinda Hasibuan; Dedi Masri; Muhammad Alfiansyah; Hikmal Akbar (CV. Alim's Publishing, 2023)
This study describes the analysis of the controversy over the meaning of nasikh and mansukh in the verses of the Qur'an according to the scholars and the analysis of the meaning of Surah Al-Imran verse: 93 according to two interpretations, Tafsir Jalalain and Tafsir Ibnu Katsir as a comparison. The type of research method used in this research is literature research or literature review to collect relevant information about the meaning of nasikh wal mansukh. The results of the research show that (1) In essence there is no disagreement among the scholars about the possibility of making changes to the law, they intend and agree that changes to the law are produced by their own ijtihad or changes made by Allah for those who argues that there are texts in the Koran, (2) From the two Tafsirs used as references in this study that Surah Al-Imran: 93, that some types of food that were forbidden to the Children of Israel were not forbidden to followers of the Shari'a of the Prophet Abraham and other prophets before the Torah lowered. This is also stated in the Torah, their own book.